Probability and statistics for engineers and scientists - Hayter, Anthony J. (Brooks/Cole, 2012)
Using many examples and data sets, this title illustrates the importance of statistical data collection and analysis for students in a variety of engineering areas as well as for students in physics, chemistry, computing, biology, management, and mathematics.